PENGARUH KEPRIBADIAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI PADA MADRASAH TSANAWIYAH SWASTA KECAMATAN WINONG KABUPATEN PATI - Nur Muhsin, 12.52.02.0226; Sutomo, Y. (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the influence of personality and motivation on the performance of teachers in non-government Islamic Junior High School (MTs Swasta)Â Winong district Pati regency with organizational culture moderated. The specific objectives of this study was to explain and to enlarge the previuos study about the influence of personality and motivation on the performance of teachers with organizational culture moderated. This study used a population of teachers in non-government Islamic Junior High School (MTs Swasta)Â Winong District Pati Regency totally 102 teachers. Sampling techniques in this study is sampling jenuh. This method used is regression with absolute difference moderation. Based on the results of the study can be summarized as follows:Â Â personality has Â a significant and positive influence on the teacher performance, motivation has Â a significant and positive influence on the teacher performance, organizational culture has Â a significant and positive influence on the teacher performance, but organizational culture do not moderate the influence of personality and motivation on the teacherâs performance.Keywords: Personality, Motivation, Organizational Culture, Teacher Performance